2016
DOI: 10.1002/pmic.201500544
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics goes forensic: Detection and mapping of blood signatures in fingermarks

Abstract: A bottom up in situ proteomic method has been developed enabling the mapping of multiple blood signatures on the intact ridges of blood fingermarks by Matrix Assisted Laser Desorption Mass Spectrometry Imaging (MALDI-MSI). This method, at a proof of concept stage, builds upon recently published work demonstrating the opportunity to profile and identify multiple blood signatures in bloodstains via a bottom up proteomic approach. The present protocol addresses the limitation of the previously developed profiling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 50 publications
0
34
0
Order By: Relevance
“…Since 2014, huge analytical efforts have been also put into the reliable detection of blood in both stains and fingermarks [16][17][18][19] , since its detection is crucial for the crime scene dynamics reconstruction within violent crimes including murders (especially with no body).…”
Section: What Information Can Be Obtained Through the Application Of mentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2014, huge analytical efforts have been also put into the reliable detection of blood in both stains and fingermarks [16][17][18][19] , since its detection is crucial for the crime scene dynamics reconstruction within violent crimes including murders (especially with no body).…”
Section: What Information Can Be Obtained Through the Application Of mentioning
confidence: 99%
“…The Home Office CAST (UK) intellectually and financially supported this idea through a PhD programme. The major outcomes were the demonstration that it is possible to detect and visualise blood protein signatures in stains and in fingermarks [17][18][19] even from very old specimens (a 9 year old blood palm print 17 and a 37 year old blood mark on fabric (Fig. 2 ) which were previously enhanced by Acid Black 1 and ninhydrin respectively.…”
Section: What Information Can Be Obtained Through the Application Of mentioning
confidence: 99%
“…In particular, the group of Simona Francese has made considerable contributions to the IMS forensic literature by using MALDI. By applying the MALDI matrix α ‐cyano‐4‐hydroxycinnamic acid by spray deposition on fingermarks, they were able to detect endogenous peptides and small proteins that enabled the determination of sex with 85% accuracy and the presence of blood . This methodology also allowed for the detection of illicit drugs and some of their metabolites …”
Section: Introductionmentioning
confidence: 99%
“…The study from Deininger et al 64 was the first in its kind to demonstrate the opportunity to link the presence of blood onto the identifying mark ridges.…”
Section: Contact (Or) Exogenous Substancesmentioning
confidence: 99%
“…Within the study 64 , it could be observed that both of the trypsin concentrations at 150 µg/mL and 200 µg/mL yielded blood signature images for Complement C3, Haemopexin, αHb and Serotransferrin (Fig. 8), with complementary efficiencies with respect to the different peptides detected and mapped; this result is to be expected given the differential abundance of the interested proteins in blood which directly For blood marks showing a higher volume of blood ("up to pools of blood"), the trypsin concentration may change again.…”
Section: Contact (Or) Exogenous Substancesmentioning
confidence: 99%